2007
DOI: 10.1108/17515630710684312
|View full text |Cite
|
Sign up to set email alerts
|

Making organizational learning happen: the value of “creative failures”

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…This means that the higher the degree of person-organization fit that is felt by lecturers, the higher the level of optimal distinctive open innovation that can be produced by lecturers, making them more open in sharing knowledge. This supports the findings of Kriegesmann et al (2007) found that when employees believe that their co-workers listen and support their ideas and relate their importance to suggestions for whatever novelty they start, they tend to display very innovative work behavior.…”
Section: Hypothesis Testingsupporting
confidence: 88%
“…This means that the higher the degree of person-organization fit that is felt by lecturers, the higher the level of optimal distinctive open innovation that can be produced by lecturers, making them more open in sharing knowledge. This supports the findings of Kriegesmann et al (2007) found that when employees believe that their co-workers listen and support their ideas and relate their importance to suggestions for whatever novelty they start, they tend to display very innovative work behavior.…”
Section: Hypothesis Testingsupporting
confidence: 88%
“…Employees of small and medium enterprises (SMEs) of Textile Industry were selected since SMEs has had a high focus on capitalizing employees’ capability to create and implement new ideas to improve product quality (Ghobadian & Gallear, 1997; Cagliano, Blackmon, & Voss, 2001; McAdam & McClelland, 2002; Enkel & Gassmann, 2010; Hotho & Champion, 2011; Brunswicker & Vanhaverbeke, 2015; Love & Roper, 2015). Moreover, while showing IWB, employees go beyond the defined concrete paths; therefore IWB is highly complex and ambiguous in nature (Kriegesmann, Kley, & Schwering, 2007). Employees show IWB only when they are supported and rewarded (Clegg, Unsworth, Epitropaki, & Parker, 2002; Janssen, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of innovation, employees may take risks by proposing new ideas, many of which could lead to organizational failure if implemented. Developing and implementing new ideas can be high risk (Ellen Mathisen, Einarsen, & Mykletun, 2012). Gong, Cheung, Wang, and Huang (2012) noted that generating new ideas does not guarantee the attainment of desired goals since most ideas fail.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Creating and conceptualizing strategic plans require thinking broadly and quickly, creating and innovating, seeking change and learning quickly (Bartram, 2005). Organizations can learn through creative errors, which enhance employees' innovation Organizational culture and strategic planning and risk-taking ability (Kriegesmann et al, 2007). Simple operational planning differs from strategic planning, as strategic plans are futuristic and associated with risks and opportunities.…”
Section: Collaborative Culture and Strategic Planningmentioning
confidence: 99%